2004
DOI: 10.1016/j.envpol.2004.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Over one hundred years of trace metal fluxes in the sediments of the Pearl River Estuary, South China

Abstract: The rapid economic development in the Pearl River Delta (PRD) region in south China in the last three decades has had a significant impact on the local environment.Estuarine sediment is a major sink for contaminants and nutrients in the surrounding ecosystem. The accumulation of trace metals in sediments may cause serious environmental problems in the aquatic system. Thirty sediment cores were collected in the Pearl River Estuary (PRE) in 2000 for a study on trace metal pollution in this region. Heavy metal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 34 publications
4
59
0
4
Order By: Relevance
“…Means and ranges of trace metal concentrations in various operationally defined geochemical fractions in the surface sediments from the PRE (Li et al, 2000a(Li et al, , 2001Liu et al, 2003) The prefixes of the sample IDs represent the locations of the samples shown in the sampling map, while the number after the prefixes correspond to the depths in the sediment profiles Pb of the sediments at the coastal zone (this study) and the PRE (Ip et al, 2004), atmospheric deposition (Wong et al, 2003) and soils in the PRD region (Wong et al, 2002) and Hong Kong , as well as natural geological sources and anthropogenic sources in the PRD (Zhu et al, 2001) (Li et al, 2000a(Li et al, , 2001Liu et al, 2003) and the surrounding coastal area (in the present study) Pb of the sediments at the coastal zone (this study) and the PRE (Ip et al, 2004), atmospheric deposition (Wong et al, 2003) and soils in the PRD region (Wong et al, 2002) and Hong Kong , as well as natural geological sources and anthropogenic sources in the PRD (Zhu et al, 2001) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Means and ranges of trace metal concentrations in various operationally defined geochemical fractions in the surface sediments from the PRE (Li et al, 2000a(Li et al, , 2001Liu et al, 2003) The prefixes of the sample IDs represent the locations of the samples shown in the sampling map, while the number after the prefixes correspond to the depths in the sediment profiles Pb of the sediments at the coastal zone (this study) and the PRE (Ip et al, 2004), atmospheric deposition (Wong et al, 2003) and soils in the PRD region (Wong et al, 2002) and Hong Kong , as well as natural geological sources and anthropogenic sources in the PRD (Zhu et al, 2001) (Li et al, 2000a(Li et al, , 2001Liu et al, 2003) and the surrounding coastal area (in the present study) Pb of the sediments at the coastal zone (this study) and the PRE (Ip et al, 2004), atmospheric deposition (Wong et al, 2003) and soils in the PRD region (Wong et al, 2002) and Hong Kong , as well as natural geological sources and anthropogenic sources in the PRD (Zhu et al, 2001) …”
Section: Discussionmentioning
confidence: 99%
“…The Pb isotopic compositions of some natural and anthropogenic sources in the region have previously been studied (Zhu, 1995;Zhu et al, 1998Zhu et al, & 2001Duzgoren-Aydin et al, 2004). The Pb isotopic composition of the surface and sub-surface sediments showed clear differentiation (Ip et al, 2004). This makes it possible to differentiate between the recent anthropogenic inputs and the natural geological Pb of the sediments in the adjacent coastal area.…”
Section: Possible Pb Sources In Sedimentsmentioning
confidence: 96%
See 2 more Smart Citations
“…The toxicological effects are further aggravated by the unique physiology of children, the sensitivity of their developing vital organs, and different chemical forms of metals involved (Hrudey et al, 1996). Other indirect consequences of trace metal contamination of the urban environment include the subsequent migration of the pollutants to receiving bodies of water via urban runoff, resulting in the trace metal enrichment of sediments (Sutherland and Tolosa, 2000;Ip et al, 2004). This may affect the quality of aquatic ecosystems and increase the body loadings of aquatic organisms through bioaccumulation and biomagnification, potentially causing trace metal contamination of the food chain (Callender and Rice, 2000).…”
Section: Introductionmentioning
confidence: 99%